Machine Learning Techniques for Cancer Prediction: A Survey - Pathak, Archana; Ruthia, Nidhi; Agrawal, Chetan (International Journal of Computer Sciences and Engineering, 2020)
In the present age of innovation medicinal field researcher are very much interested in disease classification for the analysis of disease. It is a point of concern on the grounds that real treatment of this disease isn't found till date. Patients having this ailment must be spared if and just in the event that it is found in beginning period (arrange I and stage II). In the event that it is identified in last stage (arrange III and stage IV) at that point possibility of endurance will be exceptionally less. Machine learning and information mining system will assist medicinal with handling to handle with this issue. Cancer growth has different manifestations, for example, tumor, abnormal bleeding, more weight reduction and so forth. It isn't vital that a wide range of tumors are harmful. Tumors are fundamentally of two kinds one is benign and the other one is malignant. To give suitable treatment to the patients, side effects must be contemplated appropriately and a programmed expectation framework is required which will characterize the tumor into benevolent or harmful. In the present web world, majority of information is created via web-based networking media or medicinal services sites. From this immense measure of information, side effects can be gotten by utilizing information mining method, which will be further helpful for disease location or classification. This paper makes study of such most recent research study that utilizes on the web and disconnected information for malignant growth arrangement.